On the formation of the center of tuberculosis infection in general medical units - O. V. Repinа; A. A. Golubkovа; V. A. Podgаevа (Туберкулез и болезни лёгких)
The objective of the study: to analyze the frequency of admission of tuberculosis patients to general medical units, to describe medical and social parameters of patients – sources of tuberculous mycobacteria which form a nosocomial center of tuberculosis infection.Subjects and methods. The following sources of information were used: Reporting Form no. 8 on Active Cases of Tuberculosis, data from the Annual Reporting Form on Analysis of Infectious Diseases Carrying drawn up by City Center for Medical Prevention in Yekaterinburg, Register of Infectious Diseases (Form no. 060/y), and 74 documents of Medical File of the Patient Receiving In-Patient Treatment (Form no. 003/y) for tuberculosis patients admitted to a therapy department of the city hospital.Results. Despite the decreasing tuberculosis incidence among Yekaterinburg residents, there was no significant decrease in the frequency of hospital admissions of patients with this disease to general medical units. Of all tuberculosis patients admitted to general medical units, 40.0 ± 2.7% were admitted to therapy departments. Duration of stay in a therapy department of tuberculosis patients excreting tuberculous mycobacteria made more than 7 days for 70% of such cases before they were discharged. The destruction phase was diagnosed in 56.8 ± 5.8%, 13.5 ± 4.0% had massive bacterial excretion documented by sputum microscopy. The frequency of TB/HIV co-infection made 43.2 ± 5.8%.Conclusion. In a therapy department, there is a high risk of getting infected with tuberculosis infection among patients and personnel who are exposed to a tuberculosis case.